Model of The Group Guidance Service Design Using The Cinema Therapy Method In Helping Student Achievement of Development Tasks - Hesti Permata Sari; Fitria Kasih; Citra Imelda Usman (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
The research objectives describe:1.The task profile of students' developmental achievement in class XI SMAN 3 Mukomuko. 2.Implementation of group guidance in helping the achievement of developmental tasks carried out by the Guidance and Counseling Teacher. 3.The group guidance service design model using the cinema therapy method in helping the achievement of student developmental tasks. This study uses a mixed method. Dataanalysis techniques for Development Task Inventory(ITP). While qualitative research,techniques used in data processing through data reduction,data presentation and conclusion drawing. Based on the results of research the following conclusions can be drawn:1.The profile of the task of achieving the development of students in class XI of SMAN 3 Mukomuko seen from the Inventory of Development Tasks is generally at the level of self-awareness. 2.Implementation of group guidance in assisting the achievement of developmental tasks carried out by the Guidance and Counseling Teacher,providing monotonous group guidance, discussions, homeroom. 3.Thedesign model of group guidance services using the cinema therapy method in helping the achievement of student developmental tasks. Based on the results of the research,it can be recommended that the Guidance and Counseling Teachers be able to apply the group guidance service design model using the cinema therapy method.